Effect of Oxidation on Quality of Chiba Tofu Produced by Soy Isolate Protein When Subjected to Storage - Yue Xu; Zhongjiang Wang; Baokun Qi; Anqi Ran; Zengwang Guo; Lianzhou Jiang (Foods, 2020)
Chiba tofu is a new type of vegetarian food prepared with soy protein isolate (SPI). According to factory feedback, the SPI stored in the factory storeroom in summer undergoes reactive oxidation, which changes the structure of SPI and further affects the quality of Chiba tofu. Consequently, the main objective of this study was to prepare Chiba tofu with SPI with different storage periods and evaluate the effect of different degrees of oxidation on structural characteristics of SPI and rheology, texture, microstructure and sensory properties of Chiba tofu. The carbonyl content and turbidity of SPI significantly increased, and the contents of free sulfhydryl (SH) and disulfide bond (S-S) simultaneously decreased with storage time. The oxidation changes the SPI conformation, leading to a transition of α-helix and β-turn to β-sheet and random coil during the storage periods. In the SDS–PAGE analysis, oxidation promoted the SPI molecules crosslinked and aggregated, which affected the quality of Chiba tofu. In short storage periods (0–12 days), SPI was relatively moderately oxidized when the carbonyl content was between 4.14 and 6.87 mmol/g. The storage and loss modulus of Chiba tofu both increased, the network was compact, and the hardness and springiness of Chiba tofu showed an increasing trend. Moreover, in longer storage periods (12–30 days), the SPI was relatively severely oxidized when the carbonyl content was between 7.24 and 9.14 mmol/g, which had an adverse effect on Chiba tofu rheological and texture properties, microstructure, and sensory properties. In sensory evaluation, Chiba tofu stored 12 days had the highest overall quality score than that stored on other days. This study is expected to provide an argument for the better industrial production of Chiba tofu.